Enhancing digital competence of prospective vocational teachers using project-based learning with the technological pedagigical content and knowledge approach - Setuju; Bruri Triyono, Mochamad; Muhtadi, Ali; Widowati, Asri (Edelweiss Applied Science and Technology, 2024)
Prospective teachers must prepare students with 21st-century skills using digital technology, known as digital competence. The importance of digital competence for prospective vocational teachers encourages study to develop an innovative instructional model, namely Project Based Learning (PjBL) with the technological pedagogical content and knowledge (TPACK) approach, which focuses on enhancing the digital competence of prospective teachers in vocational education. This research aims to investigate the effect of the PjBL instructional model with the TPACK approach on enhancing the digital competence of prospective vocational teachers. This study used quasi-experimental research in two universities in Yogyakarta, Indonesia. The sample used was 102 prospective vocational teachers consisting of 45 prospective teachers in the control class and 57 prospective teachers in the experimental class. The digital competency measurement items include 30 statements. Data analysis in this study used an independent t-test. The results of the independent t-test conclude that there was a significant difference. The results concluded that the post-test digital competency score of the experimental group students increased with a score of 79.19, while the control group 58.39. The practical implication of the application of this model is that educators can apply it to improve the competence of prospective vocational teachers with indicators relevant to the material through learning media creation project activities. Recommendations for further research are to compare the effectiveness of PjBL with various other instructional models with the TPACK approach to develop digital competence of prospective teachers and involve wider samples such as between regions or countries.